Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Associations Between Complementary Feeding Approach, Dietary Intake, and Growth: A Secondary Analysis of the Maternal and Infant Nutrition Trial - Kinzie L. Matzeller; Mikayla L. Hernandez; Gabrielle N.E. Glime; Claudia A. Schaefer; Edward L. Melanson; Daniel N. Frank; Audrey E. Hendricks; Nancy F. Krebs; Minghua Tang (Journal of the Academy of Nutrition and Dietetics, 2026)

The effects of U.S. poultry industry consolidation on employee productivity and labor costs - Tina L. Saitone; K. Aleks Schaefer; Daniel P. Scheitrum; Shawn Arita; Vince Breneman; Rebecca Nemec Boehm (Food Policy, 2026)

Recovery of tree-related microhabitats in a tropical rainforest after agricultural abandonment - Ronja Hausmann; Sebastián Escobar; Nico Blüthgen; H. Martin Schaefer; Felicity L. Newell; Maria-José Endara; Juan Ernesto Guevara-Andino; Heike Feldhaar; Daniel Kraus; Dominik Thom; Jörg Müller (Biological Conservation, 2026)

Simulated atmospheric transformation of the tire additives in the aqueous phase: 6-PPD, 6-PPD quinone, diphenylguanidine, and dicyclohexylamine - Volkwin Kuntz; Natalie Kamprad; Bettina Seiwert; Thomas Schaefer; Hartmut Herrmann; Thorsten Reemtsma; Daniel Zahn (Environmental Pollution, 2026)

Non-destructive surface sampling of PFAS exposure on firefighter protective gears: Potential implications for occupational exposure - Christian Alejandro Hernandez-Fajardo; Maria Guerra de Navarro; Olutobi Daniel Ogunbiyi; Paola Louzado-Feliciano; Natasha Schaefer Solle; Erin Kobetz; Alberto J. Caban-Martinez; Natalia Quinete (Journal of Hazardous Materials, 2026)

Corrigendum to “Application of sensing techniques for quantifying CO2 flux and dynamics in environments affected by the Fundão dam collapse, Mariana, Brazil” [J. S. Am. Earth Sci. 146 (2024) 105099 – pages 1–9] - Heitor Paiva Palma; Danilo César de Mello; Márcio Rocha Francelino; Daniela Schmitz; Gustavo Vieira Veloso; Ana Paula Marinho Santos; Daniel Nunes Krum; André Thomazini; Elpídio Inácio Fernandes-Filho; Carlos Ernesto Gonçalves Reynaud Schaefer; José A.M. Demattê (Journal of South American Earth Sciences, 2025)

Soil and vegetation types are predisposition factors controlling greenness changes: A shift of paradigm in greening and browning modelling? - Luís Flávio Pereira; Elpídio Inácio Fernandes-Filho; Lucas Carvalho Gomes; Daniel Meira Arruda; Guilherme Castro Oliveira; Carlos Ernesto Gonçalves Reynald Schaefer; José João Lelis Leal de Souza; Márcio Rocha Francelino (Remote Sensing Applications: Society and Environment, 2024)

Application of sensing techniques for quantifying CO2 flux and dynamics in environments affected by the fundão dam collapse, mariana, Brazil - Heitor Paiva Palma; Danilo César de Mello; Márcio Rocha Francelino; Daniela Schmitz; Gustavo Vieira Veloso; Ana Paula Marinho Santos; Daniel Nunes Krum; André Thomazini; Elpídio Inácio Fernandes-Filho; Carlos Ernesto Gonçalves Reynaud Schaefer; Teogenes Senna de Oliveira; José A.M. Demattê (Journal of South American Earth Sciences, 2024)

Disentangling the effects of electroporation and heat during pulsed electric field (PEF) processing of oat-based milk alternative: A case study on Lactiplantibacillus plantarum inactivation - Arisa Thamsuaidee; Eva Schaefer; Daniel Schneider; Claudia Siemer; Vasilis P. Valdramidis (Innovative Food Science & Emerging Technologies, 2024)

The challenge of assessing the effects of drifting fish aggregating devices on the behaviour and biology of tropical tuna - Amaël Dupaix; Frédéric Ménard; John D. Filmalter; Yannick Baidai; Nathalie Bodin; Manuela Capello; Emmanuel Chassot; Hervé Demarcq; Jean‐Louis Deneubourg; Alain Fonteneau; Fabien Forget; Francesca Forrestal; et al. (Fish and Fisheries, 2024)
Fishers have intensively used drifting fish aggregating devices (DFADs) over the last three decades to facilitate their catch of tropical tunas. DFADs increase purse‐seine efficiency, potentially increasing tuna fishing mortality. They could also have impacts on tuna natural mortality and reproductive potential, and assessing the consequences of their presence at sea on tuna populations is a challenge. The use of DFADs results in a major increase in the number of floating objects, which are spatially heterogeneous at sea. To date, no converging scientific results exist regarding the effects of DFADs on the large‐scale movements and behaviour of tuna, mainly due to the difficulty of disentangling the respective roles of DFADs and environmental factors. Some biological indices show that tuna condition is lower when associated to a floating object than in a free‐swimming school. However, it is not clear whether this is the cause or the consequence of the association nor if it has long‐term effects on individuals' fitness. Further scientific progress requires (i) the collection of time series of indicators to monitor habitat change, individual behaviour, individual fitness, and population dynamics and (ii) experimental studies to identify the underlying behavioural and biological processes involved in associative behaviour. The extent of the modification of the surface habitat by the massive deployment of DFADs and the current uncertainty of the possible long‐term consequences on the individual fitness and dynamics of tuna populations argue for the need for increased awareness of this issue by Regional Fisheries Management Organisations regulating tuna fishing.

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Highly active fish in low oxygen environments: vertical movements and behavioural responses of bigeye and yellowfin tunas to oxygen minimum zones in the eastern Pacific Ocean - Nicolas E. Humphries; Daniel W. Fuller; Kurt M. Schaefer; David W. Sims (Marine Biology, 2024)
Oxygen minimum zones in the open ocean are predicted to significantly increase in volume over the coming decades as a result of anthropogenic climatic warming. The resulting reduction in dissolved oxygen (DO) in the pelagic realm is likely to have detrimental impacts on water-breathing organisms, particularly those with higher metabolic rates, such as billfish, tunas, and sharks. However, little is known about how free-living fish respond to low DO environments, and therefore, the effect increasing OMZs will have cannot be predicted reliably. Here, we compare the responses of two active predators (bigeye tuna Thunnus obesus and yellowfin tuna Thunnus albacares ) to DO at depth throughout the eastern Pacific Ocean. Using time-series data from 267 tagged tunas (59,910 days) and 3D maps of modelled DO, we find that yellowfin tuna respond to low DO at depth by spending more time in shallower, more oxygenated waters. By contrast, bigeye tuna, which forage at deeper depths well below the thermocline, show fewer changes in their use of the water column. However, we find that bigeye tuna increased the frequency of brief upward vertical excursions they performed by four times when DO at depth was lower, but with no concomitant significant difference in temperature, suggesting that this behaviour is driven in part by the need to re-oxygenate following time spent in hypoxic waters. These findings suggest that increasing OMZs will impact the behaviour of these commercially important species, and it is therefore likely that other water-breathing predators with higher metabolic rates will face similar pressures. A more comprehensive understanding of the effect of shoaling OMZs on pelagic fish vertical habitat use, which may increase their vulnerability to surface fisheries, will be important to obtain if these effects are to be mitigated by future management actions.

A single rapid heat stress episode does not result in prolonged elevations in salivary cortisol and C-reactive protein production in firefighters - Cory J. Coehoorn; Diana Cruz; Schaefer Mueller; Lilly Anne D. Kamberov; Jillian Danzy; Naina Bouchereau-Lal; Daniel Poole; Aaron Adams (Journal of Thermal Biology, 2024)

Facilitation of non-indigenous ascidian by marine eco-engineering interventions at an urban site - Nina Schaefer; Francisco Sedano; Melanie J. Bishop; Kate Dunn; M. Hank Haeusler; K. Daniel Yu; Yannis Zavoleas; Katherine A. Dafforn (Biofouling, 2023)

Why is Brachiaria decumbens Stapf. a common species in the mining tailings of the Fundão dam in Minas Gerais, Brazil? - Daniel Rodrigues da Silva; Carlos Ernesto Gonçalves Reynaud Schaefer; Kacilda Naomi Kuki; Michel Filiphy Silva Santos; Gustavo Heringer; Luzimar Campos da Silva (Environmental Science and Pollution Research, 2022)

AudioGene: refining the natural history of KCNQ4, GSDME, WFS1, and COCH-associated hearing loss - Ryan K. Thorpe; W. Daniel Walls; Rae Corrigan; Amanda Schaefer; Kai Wang; Patrick Huygen; Thomas L. Casavant; Richard J. H. Smith (Human Genetics, 2022)

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Horizontal movements, utilization distributions, and mixing rates of yellowfin tuna ( Thunnus albacares ) tagged and released with archival tags in six discrete areas of the eastern and central Pacific Ocean - Kurt M. Schaefer; Daniel W. Fuller (Fisheries Oceanography, 2022)
A total of 1522 yellowfin tuna, Thunnus albacares , were captured, tagged, and released with surgically implanted archival tags (ATs), in six discrete areas of the eastern and central Pacific Ocean, during 2002 through 2019. Of 483 ATs returned (31.7%), 227 ATs from yellowfin (48–147 cm in fork length) at liberty from 32 to 1846 d ( = 300.1 d) provided suitable data sets which were processed using an unscented Kalman filter model with sea‐surface temperature measurements integrated (UKFsst) in order to obtain most probable tracks and movement parameters. Although some differences were observed in the movement patterns for fish from within and among the six release areas, 99% of the 227 fish remained within 1000 M of their release locations, indicating limited dispersion and fidelity to release locations. The median movement parameter D , which defines dispersion from the UKFsst model, for the fish released in the offshore equatorial areas showed much greater dispersion rates compared to those for the fish released along the coast or around islands. The rates of mixing of yellowfin among the release areas were found to be dependent on the distances between release areas, with, in general, the greatest mixing occurring among areas in closest proximity, whereas for the two areas offshore Mexico and the two offshore equatorial areas, the rates of mixing were nonexistent or negligible.

A comparative analysis of genetic hearing loss phenotypes in European/American and Japanese populations - W. Daniel Walls; Hideaki Moteki; Taylor R. Thomas; Shin-ya Nishio; Hidekane Yoshimura; Yoichiro Iwasa; Kathy L. Frees; Carla J. Nishimura; Hela Azaiez; Kevin T. Booth; Robert J. Marini; Diana L. Kolbe; et al. (Human Genetics, 2020)

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Methodology for the Semi-quantitative Evaluation of Geoheritage Applied to Coastal Geotourism in João Pessoa (Paraíba, Northest Brazil) - Luciano Schaefer Pereira; Daniel Matos de Carvalho; Lúcio Sobral da Cunha (Geoheritage, 2019)

Correction to: Recent progress in European percid fish culture production technology—tackling bottlenecks - Tomas Policar; Fabian J. Schaefer; Edson Panana; Stefan Meyer; Stefan Teerlinck; Damien Toner; Daniel Żarski (Aquaculture International, 2019)

Recent progress in European percid fish culture production technology—tackling bottlenecks - Tomas Policar; Fabian J. Schaefer; Edson Panana; Stefan Meyer; Stefan Teerlinck; Damien Toner; Daniel Żarski (Aquaculture International, 2019)

Above Water Electric Potential Signatures of Submerged Naval Vessels - David Schaefer; Christian Thiel; Jens Doose; Andreas Rennings; Daniel Erni (Journal of Marine Science and Engineering, 2019)
In this paper, we investigate the fundamental linkage between underwater electric potential (UEP) signatures and their related electric fields above the waterline, which are introduced as above water electric potential (AEP) signatures. As a first step, the field distribution for an underwater point source excitation (fundamental solution) is derived analytically, using an adjusted method of images. Subsequently a numerical approach is introduced, whereby the calculation of the stationary current density distribution and electrostatic fields are coupled within an FEM simulation. Simulation results are presented for the aforementioned point source, as well as for a submarine model, where the latter includes considering non-linear polarization curves to model the electrochemical behavior at the metal–seawater interface. Finally, the relevance of AEP signatures in the context of anti-submarine warfare (ASW) is discussed. Our results show that AEP signatures inevitably occur along with UEP signatures, and could therefore in principal be used to detect submerged submarines via airborne sensors. However, an estimation of the expectable signal-to-noise-ratio (SNR) suggests that AEP signatures are difficult to exploit and therefore entail a much lower risk compared to other signatures.

The growth cessation model: a growth model for species showing a near cessation in growth with application to bigeye tuna (Thunnus obesus) - Mark N. Maunder; Richard B. Deriso; Kurt M. Schaefer; Daniel W. Fuller; Alexandre M. Aires-da-Silva; Carolina V. Minte-Vera; Steven E. Campana (Marine Biology, 2018)

Investigation of a Worker Death While Agitating Manure in a Non-enclosed Storage - John M. Shutske; Daniel Schaefer; Rebecca Larson; Kevin Erb; Cheryl Skjolaas; Stephanie Leonard; Jeff Nelson; Elizabeth Binversie; Scott Rifleman (Journal of Agromedicine, 2018)

Vegetation cover of Brazil in the last 21 ka: New insights into the Amazonian refugia and Pleistocenic arc hypotheses - Daniel M. Arruda; Carlos E. G. R. Schaefer; Rúbia S. Fonseca; Ricardo R. C. Solar; Elpídio I. Fernandes‐Filho (Global Ecology and Biogeography, 2018)
Aim The two main hypotheses about the Neotropical palaeovegetation, namely that of Amazonian refugia by Haffer and of the Pleistocene arc by Prado and Gibbs, are still constantly debated. We offer new insights on this debate using ecological niche modelling with combined climate–soil predictors to test both hypotheses, reconstruct the palaeovegetation of the Last Glacial Maximum (LGM; 21 ka) and Mid‐Holocene (Mid‐H; 6 ka) and indicate the configuration of refugia areas. Location Brazil. Time period Last 21 ka. Major taxa studied Biomes. Methods We modelled the environmental space of the 10 most representative biomes with the RandomForest classifier, using climate predictors from three atmospheric general circulation models (CCSM4, MPI‐ESM‐P and MIROC‐ESM) and soil predictors, the same for the different situations. Based on the consensus among the models, we reconstructed the palaeovegetation cover for LGM and Mid‐H and used fossil pollen sites to validate the reconstructions in a direct comparison. Results The climate in the past was cooler and wetter throughout most of the territory. The Amazon basin region was the most affected by climate change in the last 21 ka, with equatorial rain forest retracting to refugia areas, while the tropical rain forest (with climatic preferences similar to the Atlantic forest) expanded in the basin. In southern Brazil, the mixed forest ( Araucaria forest) shifted to lower latitudes, while the grasslands expanded. In most biomes, the greatest changes occurred in the ecotonal zones, supported by pollen fossils. Main conclusions With regard to Haffer's hypothesis, the forests of the Amazonian lowlands retreated to refugia areas, while the colder and wetter climate of the basin created a favourable niche for another type of forest, instead of savanna. The advance of dry vegetation was restricted to ecotonal conditions, preventing the formation of a continuous Pleistocene arc, predicted by Prado and Gibbs's hypothesis.

Post-catastrophe Analysis of the Fundão Tailings Dam Failure in the Doce River System, Southeast Brazil: Potentially Toxic Elements in Affected Soils - Marcelo Braga Bueno Guerra; Brian T. Teaney; Brianna J. Mount; Daniel J. Asunskis; Brennan T. Jordan; Ryan J. Barker; Eliana E. Santos; Carlos Ernesto G. R. Schaefer (Water, Air, & Soil Pollution, 2017)

Emergent climate and CO 2 sensitivities of net primary productivity in ecosystem models do not agree with empirical data in temperate forests of eastern North America - Christine R. Rollinson; Yao Liu; Ann Raiho; David J. P. Moore; Jason McLachlan; Daniel A. Bishop; Alex Dye; Jaclyn H. Matthes; Amy Hessl; Thomas Hickler; Neil Pederson; Benjamin Poulter; et al. (Global Change Biology, 2017)
Ecosystem models show divergent responses of the terrestrial carbon cycle to global change over the next century. Individual model evaluation and multimodel comparisons with data have largely focused on individual processes at subannual to decadal scales. Thus far, data‐based evaluations of emergent ecosystem responses to climate and CO 2 at multidecadal and centennial timescales have been rare. We compared the sensitivity of net primary productivity ( NPP ) to temperature, precipitation, and CO 2 in ten ecosystem models with the sensitivities found in tree‐ring reconstructions of NPP and raw ring‐width series at six temperate forest sites. These model‐data comparisons were evaluated at three temporal extents to determine whether the rapid, directional changes in temperature and CO 2 in the recent past skew our observed responses to multiple drivers of change. All models tested here were more sensitive to low growing season precipitation than tree‐ring NPP and ring widths in the past 30 years, although some model precipitation responses were more consistent with tree rings when evaluated over a full century. Similarly, all models had negative or no response to warm‐growing season temperatures, while tree‐ring data showed consistently positive effects of temperature. Although precipitation responses were least consistent among models, differences among models to CO 2 drive divergence and ensemble uncertainty in relative change in NPP over the past century. Changes in forest composition within models had no effect on climate or CO 2 sensitivity. Fire in model simulations reduced model sensitivity to climate and CO 2 , but only over the course of multiple centuries. Formal evaluation of emergent model behavior at multidecadal and multicentennial timescales is essential to reconciling model projections with observed ecosystem responses to past climate change. Future evaluation should focus on improved representation of disturbance and biomass change as well as the feedbacks with moisture balance and CO 2 in individual models.

Combining climatic and soil properties better predicts covers of Brazilian biomes - Daniel M. Arruda; Elpídio I. Fernandes-Filho; Ricardo R. C. Solar; Carlos E. G. R. Schaefer (The Science of Nature, 2017)

Erratum to: Lack of functional P2X7 receptor aggravates brain edema development after middle cerebral artery occlusion - Melanie Kaiser; Anja Penk; Heike Franke; Ute Krügel; Wolfgang Nörenberg; Daniel Huster; Michael Schaefer (Purinergic Signalling, 2016)

Lack of functional P2X7 receptor aggravates brain edema development after middle cerebral artery occlusion - Melanie Kaiser; Anja Penk; Heike Franke; Ute Krügel; Wolfgang Nörenberg; Daniel Huster; Michael Schaefer (Purinergic Signalling, 2016)

Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Fernando A. O. Silveira; Daniel Negreiros; Newton P. U. Barbosa; Elise Buisson; Flávio F. Carmo; Daniel W. Carstensen; Abel A. Conceição; Tatiana G. Cornelissen; Lívia Echternacht; G. Wilson Fernandes; Queila S. Garcia; Tadeu J. Guerra; et al. (Plant and Soil, 2016)

The strength of weak connections in the macaque cortico-cortical network - Alexandros Goulas; Alexander Schaefer; Daniel S. Margulies (Brain Structure and Function, 2015)

Land use intensification alters ecosystem multifunctionality via loss of biodiversity and changes to functional composition - Eric Allan; Pete Manning; Fabian Alt; Julia Binkenstein; Stefan Blaser; Nico Blüthgen; Stefan Böhm; Fabrice Grassein; Norbert Hölzel; Valentin H. Klaus; Till Kleinebecker; E. Kathryn Morris; et al. (Ecology Letters, 2015)
Global change, especially land‐use intensification, affects human well‐being by impacting the delivery of multiple ecosystem services (multifunctionality). However, whether biodiversity loss is a major component of global change effects on multifunctionality in real‐world ecosystems, as in experimental ones, remains unclear. Therefore, we assessed biodiversity, functional composition and 14 ecosystem services on 150 agricultural grasslands differing in land‐use intensity. We also introduce five multifunctionality measures in which ecosystem services were weighted according to realistic land‐use objectives. We found that indirect land‐use effects, i.e. those mediated by biodiversity loss and by changes to functional composition, were as strong as direct effects on average. Their strength varied with land‐use objectives and regional context. Biodiversity loss explained indirect effects in a region of intermediate productivity and was most damaging when land‐use objectives favoured supporting and cultural services. In contrast, functional composition shifts, towards fast‐growing plant species, strongly increased provisioning services in more inherently unproductive grasslands.

Movements, behavior, and habitat utilization of yellowfin tuna ( Thunnus albacares ) in waters surrounding the R evillagigedo I slands A rchipelago B iosphere R eserve, M exico - Kurt M. Schaefer; Daniel W. Fuller; Gabriel Aldana (Fisheries Oceanography, 2014)
The movements, behavior, and habitat utilization of yellowfin tuna, Thunnus albacares , following capture and release with archival tags in the Revillagigedo Islands Archipelago Biosphere Reserve ( RIABR ), Mexico, are described from analyses of 16 578 days of time‐series data, downloaded from 52 archival tags recovered from yellowfin (78–173 cm in length and 1.7–8.0 yr of age) at liberty from 93 to 1773 days ( = 411 days), collected during 2006–2012. An unscented K alman filter model with sea‐surface temperature measurements integrated ( UKF sst) was used to process the archival tag data sets to obtain improved estimates of geographic positions, most probable tracks ( MPT s), and movement parameters. The MPT s indicate restricted movements, low levels of dispersion, and fidelity of yellowfin tuna to the RIABR . The median parameter estimates from the UKF sst model for errors in longitude (σ x ) and latitude (σ y ) were 0.46° and 1.84°, respectively, for directed movements ( u and v ) –0.05 NM day −1 and –0.05 NM day −1 , respectively, and for dispersive movement ( D ) 117.99 NM 2 day −1 . Analyses of daily timed depth and temperature records resulted in the classification of the data into four distinct behaviors. There are significant differences among ages in the durations of Type I and Type II diving behaviors and in the daytime and nighttime vertical habitat utilization distributions. The oceanography surrounding the RIABR appears to have a profound influence on the movements, behavior, and habitat utilization of yellowfin in this area.

Simultaneous behavior of skipjack (Katsuwonus pelamis), bigeye (Thunnus obsesus), and yellowfin (T. albacares) tunas, within large multi-species aggregations associated with drifting fish aggregating devices (FADs) in the equatorial eastern Pacific Ocean - Kurt M. Schaefer; Daniel W. Fuller (Marine Biology, 2013)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Vertical movements, behavior, and habitat of bigeye tuna (Thunnus obesus) in the equatorial eastern Pacific Ocean, ascertained from archival tag data - Kurt M. Schaefer; Daniel W. Fuller (Marine Biology, 2010)

Purification and properties of Sandercyanin, a blue protein secreted in the mucus of blue forms of walleye, Sander vitreus - Chi-Li Yu; Daniel Ferraro; S. Ramaswamy; Mark H. Schmitz; Wayne F. Schaefer; David T. Gibson (Environmental Biology of Fishes, 2008)

Movements, behavior, and habitat utilization of yellowfin tuna (Thunnus albacares) in the northeastern Pacific Ocean, ascertained through archival tag data - Kurt M. Schaefer; Daniel W. Fuller; Barbara A. Block (Marine Biology, 2007)

Effects of Barriers and Thermal Refugia on Local Movement of the Threatened Leopard Darter, Percina pantherina - Jacob F. Schaefer; Edie Marsh-Matthews; Daniel E. Spooner; Keith B. Gido; William J. Matthews (Environmental Biology of Fishes, 2003)

Detection of Giardia in Environmental Waters by Immuno-PCR Amplification Methods - Meena H. Mahbubani; Frank W. Schaefer III; Daniel D. Jones; Asim K. Bej (Current Microbiology, 1998)